Chiral Dicarboxamide Scaffolds Containing a Sulfiliminyl Moiety as Potential Ryanodine Receptor Activators - Zhou, Sha; Jia, Zhehui; Xiong, Lixia; Yan, Tao; Yang, Na; Wu, Guiping; Song, Haibin; Li, Zhengming (Journal of agricultural and food chemistry, 2014)
To search for new environmentally benign insecticides with high activity, low toxicity, and low residue, novel chiral configurations introduced into dicarboxamide scaffolds containing N-cyano sulfiliminyl moieties were first studied. Four series of phthalamides with sulfur-containing side chains were designed, synthesized, and evaluated against oriental armyworm (Pseudaletia separata Walker) and diamondback moth (Plutella xylostella (L.)) for their insecticidal activities. All structures were characterized by 1H NMR, 13C NMR, and HRMS (or elemental analysis), and their configurations were confirmed by optical polarimetry. The biological assessment indicated that some title compounds exhibited significant insecticidal activities. For oriental armyworm, these stereoisomers exerted different impacts on biological activity following the sequence (Sc, Ss) ≥ (Sc, Rs) ≫ (Rc, Ss) > (Rc, Rs), and carbon chirality influenced the activities more strongly than sulfur. Compounds Ia and IIa reached as high an activity as commercial flubendiamide, with LC50 values of 0.0504 and 0.0699 mg L–1, respectively, lower than that of flubendiamide (0.1230 mg L–1). For diamondback moth, the sequence of activity was (Sc, Ss) > (Sc, Rs), and the sulfur chirality influenced the activities more greatly than carbon. Compound IIe exhibited even higher activity than flubendiamide, whereas Ie and Ic,d reached the activity of the latter. The results indicated that the improvement of insecticidal activity probably required a coordination of both carbon and sulfur chirality. Comparative molecular field analysis calculation indicated that stereoisomers with Sc configurations containing strong electron-withdrawing groups such as as CN are important in maintaining the high activity. The chiral scaffolds containing the N-cyano sulfiliminyl moiety are also essential for high larvicidal activity. Some title compounds could be considered as potential candidates for ryanodine receptor activators.